Analisis Cemaran Logam Berat dalam Buah Ananas comosus (L.) Merr. Kaleng secara Spektrofotometri Serapan Atom - Setyorini Sugiastuti; Sediarso Sediarso; Wila Lesthia Kharisma (Fakultas Farmasi Universitas Pancasila, 2006)
This study evaluated heavy metal contamination (lead, copper and cadmium) of canned pineapple. The research was done towards some canned pineapples with different expiry date, one year, two years and three years using wet digestion and atomic absorption spectrophotometry. The result showed that the lead contamination values of 1, 2 and 3 years expiry date canned pineaplles are 0.93 ppm, 0.73 ppm and 0.23 ppm. The copper contamination values are 2.15 ppm, 1.56 ppm, 0.92 ppm while the cadmium contamination values are 0.02 ppm, 0.02 ppm, 0.01 ppm. The closer to the expiry date, the higher values of heavy metal contamination.